Interferensi Fonologi dan Morfologi Bahasa Makassar terhadap Bahasa Indonesia dalam Podcast Warung Kopi - Azzahrah, Siti Fatimah; Fiddienika, Arief (Universitas Muhammadiyah Surabaya, 2024)
This research aims to describe the manifestation of interference by Makassar speakers towards Indonesian at the phonological and morphological levels that occurs in one episode of the Podcast Warung Kopi. This type of research is descriptive qualitative, and the data collected are words recorded after listening to the Podcast Warung Kopi, not data that is numbers. As a result of the research, it was found that speakers often made mistakes in phonology and morphology, because they incorporated elements of the Makassar language into Indonesian in their speech. The research findings on phonological interference include 22 data which are divided into three categories: reduction of phoneme sounds, addition of phoneme sounds, and replacement of phoneme sounds. In this study, there were 6 morphological interferences found, where the morphological interference occurred at the affixation level